Intermittent waste heat recovery via ORC in coffee torrefaction - Pantaleo,AM; Fordham,J; Oyewunmi,OA; Markides,CN (Elsevier, 2017)
Coffee torrefaction is carried out by means of hot air at average temperature of 200-240°C and with intermittent cycles where a lot of heat is discharged from the stack. CHP systems have been investigated to provide heat to the process. However, much of the heat released in the process is from the afterburner that heats up the flue gas to higher temperatures to remove volatile organic compounds and other pollutants. In this paper, the techno-economic feasibility of utilising waste heat from a rotating drum coffee roasting with partial hot gas recycling is assessed. A cost analysis is adopted to compare the profitability of two systems configurations integrated into the process. The case study of a major coffee torrefaction firm with 500 kg/hr production capacity in the Italian energy framework is taken. The CHP options under investigation are: (i) regenerative topping micro gas turbine (MGT) coupled to the existing modulating gas burner to generate hot air for the roasting process; (ii) intermittent waste heat recovery from the hot flue gas through an organic Rankine cycle (ORC) coupled to a thermal storage buffer. The results show that the profitability of these investments is highly influenced by the natural gas/electricity cost ratio, by the coffee torrefaction production capacity and intermittency level of discharged heat. In this case study, MGT seems to be more profitable than waste heat recovery via ORC due to the intermittency of the heat source and the relatively high electricity/heat cost ratio.